Efficient photocatalytic degradation of Rhodamine B by a novel CeO2/Bi2WO6 composite film - Issarapanacheewin S. (2017)
© 2016 Elsevier B.V. The CeO 2 , Bi 2 WO 6 and 0.4CeO 2 /0.6Bi 2 WO 6 photocatalyst films were fabricated by a doctor blading method. The film thickness of the as-prepared samples was varied to one, two and three layers. The physicochemical properties of all sample films were characterization by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), UV–vis spectroscopy, and photoluminescence (PL) techniques. Photocatalytic activities of CeO 2 , Bi 2 WO 6 and 0.4CeO 2 /0.6Bi 2 WO 6 films were investigated via the degradation of Rhodamine B (RhB) under visible light irradiation. The three-layered films of 0.4CeO 2 /0.6Bi 2 WO 6 composite exhibit the highest photocatlytic activity. It was found that the synergistic effect of CeO 2 and Bi 2 WO 6 causes the enhanced photocatalytic activity of 0.4CeO 2 /0.6Bi 2 WO 6 composite by improving efficiency of interfacial charge transfer process. The formation of hydroxyl radicals (OH) on the surface of visible-light illuminated the composite film was detected by the luminescence technique using terephthalic acid as probe molecules. Based on the results of the present study, a reasonable mechanism of photocatalysis on CeO 2 /Bi 2 WO 6 composite under visible light was proposed.